Analisis Strategi Pengelolaan Wakaf Sebagai Bisnis Sosial Islam Pesantren Nurul Iman - Khoirun Nisa; Sarwo Edi (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze Waqf Management Strategy as Islamic Social Business at Nurul Iman Islamic Boarding School. at the Nurul Iman Islamic Boarding School, the data source for this research is primary data obtained from observation and interviews, the data analysis technique used in this study is SWOT analysis, while the result of this research is that the Nurul Iman Islamic Boarding School has Waqf that can be empowered and Waqf is Still can be developed, the weakness in the form of unproductive human resources and unproductive management, has the potential for waqf which can still develop, has the potential to attract more donations and waqf can be used as a business unit, and the main threat is public distrust and a lack of socialization/work from other institutions.